2019
DOI: 10.3390/en12071255
|View full text |Cite
|
Sign up to set email alerts
|

NOx Reduction in Diesel-Hydrogen Engines Using Different Strategies of Ammonia Injection

Abstract: In order to reduce NOx emissions in internal combustion engines, the present work analyzes a measurement which consists of injecting ammonia directly into the combustion chamber. A commercial compression ignition engine fueled with a hydrogen-diesel blend was studied numerically. It was verified that the flow rate shape in which the ammonia was injected, particularly rectangular, triangular, or parabolic, as well as the injection duration had an important influence on NOx reduction. A 11.4% improvement in NOx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Combustion of gases that contain hydrogen [5,6] occupies a significant role for clean and efficient energy supply. Hydrogen allows a useful way of storing the surplus power generated by photovoltaics and wind [7].…”
Section: Introductionmentioning
confidence: 99%
“…Combustion of gases that contain hydrogen [5,6] occupies a significant role for clean and efficient energy supply. Hydrogen allows a useful way of storing the surplus power generated by photovoltaics and wind [7].…”
Section: Introductionmentioning
confidence: 99%
“…A value of −18º CA ATDC leads to important NO x reduction with a noticeable SFC penalty. Basically, the NO x reduction achieved with a high pre-injection rate or by a late pre-injection rate is reached through a reduction in the combustion temperature, since the high combustion temperatures reached in the combustion chamber are responsible for most NO x emitted to the atmosphere [41,42]. On the other hand, the entropy method provides case 25 as the most appropriate injection pattern, with a −22º CA ATDC pre-injection starting instant, 25% pre-injection rate, and 5º CA pre-injection duration.…”
Section: Standard Deviation Weighting Methodsmentioning
confidence: 99%
“…In CFD, it is common to employ the so called extended Zeldovich mechanism [48,49], based on 3 reactions and 7 species. Nevertheless, previous works [44,50] compared several kinetic schemes using experimental results and concluded that the model of Yang et al provides satisfactorily accurate results.…”
Section: Nox Formation Kinetic Schemementioning
confidence: 99%